Effects of molecular crowding on stretching of polymers in poor solvent - Singh, A.R.; Giri, D.; Kumar, S. (My University, 2009)
We consider a linear polymer chain in a disordered environment modeled by percolation clusters on a square lattice. The disordered environment is meant to roughly represent molecular crowding as seen in cells. The model may be viewed as the simplest representation of biopolymers in a cell. We show the existence of intermediate states during stretching arising as a consequence of molecular crowding. In the constant distance ensemble the force-extension curves exhibit oscillations. We observe the emergence of two or more peaks in the probability distribution curves signaling the coexistence of different states and indicating that the transition is discontinuous unlike what is observed in the absence of molecular crowding.
Keywords: Biopolymers; Linear polymer chains; Molecular crowding; Poor solvents; Probability distributions